Os estrangeiros e suas histórias no caminho dos Kinja - FOLHES, Rodrigo Theophilo (2018)
This work resizes the ethnohistory of the Kinja (Waimiri-Atroari) indigenous people, inhabitants of the headwaters of the left bank of the lower Negro river and the headwaters of the upper Uatumã river. Much of what has been written about them from the 1970s onwards was that the collapse of their social system was brought about by the collision with the state's expanding fronts, which were skyrocketing in the Amazon. Through the ethnography of the descriptions of chroniclers, naturalists, indigenists and anthropologists I seek to reflect on the construction of otherness marked by cultural, political, economic and epistemological processes. Anthropologist Stephen Baines' thesis led me to discuss the history of Kinja's past contacts with the agents of civilization in order to better situate historically and understand sociologically the subordination / domination pair that guides the analyzes of this anthropologist. From new contexts and challenges posed to anthropological practice, I seek to go beyond the framing of losses, namely, the annihilation of the “Waimiri-Atroari”.